"Doors Started to Appear:" A Methodological Framework for Analyzing Visuo-Verbal Data Drawing on Roland Barthes's Classification of Text-Image Relations. (17th March 2022) - Grange, Huw; Lian, Olaug S.
Following a "visual turn" in qualitative methods, photographs and other forms of visual expression are increasingly used in conjunction with verbal data in social science research. According equal status to visual and verbal artifacts, however, poses significant methodological challenges. "Photo elicitation" methods, which typically privilege participants' interpretations of photographs over the photographs themselves, have dominated. This article answers calls for greater reflection on and transparency in the analysis of data across multiple modes of expression. Building on previous approaches, we propose an analytical framework for interpreting visuo-verbal research data that draws on Roland Barthes's tripartite classification of text-image relations into "illustration, " "anchorage, " and "relay." We explore how our framework can be put into practice by applying it to photographs and written texts generated as part of the "Living with an eating disorder during the COVID-19 pandemic" project, focusing on three settings represented by participants: the hospital ward, the home, and natural environments. We subsequently reflect on some of the strengths and limitations of our framework in light of its application and with respect to established approaches to analyzing visuo-verbal data. Our framework of Text-Image Relations Analysis enables researchers to explore text-image relations as constitutive of meaning without privileging one semiotic mode over the other. As with all qualitative researcher, however, careful delineation of the meaning-making roles of participants and researchers is key.